2009
DOI: 10.1051/0004-6361/200811328
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances of 451 stars from the HARPS GTO planet search program

Abstract: We present a uniform study of the chemical abundances of 12 elements (Si, Ca, Sc, Ti, V, Cr, Mn, Co, Ni, Na, Mg, and Al) derived from the spectra of 451 stars observed as part of one of the HARPS GTO planet search programs. Sixty eight of these are planetbearing stars. The main goals of our work are: i) the investigation of possible differences between the abundances of stars with and without planets; ii) the study of the possible differences in the abundances of stars in the thin and the thick disc. We confir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
239
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 155 publications
(286 citation statements)
references
References 37 publications
44
239
1
2
Order By: Relevance
“…The average error in the [α/Fe] ratio is 0.05 dex. We note that, in general, our derived abundances agree with the [α/Fe] presented in the literature (see Neves et al 2009;Adibekyan et al, in prep. ).…”
Section: α Element Abundancesupporting
confidence: 90%
See 1 more Smart Citation
“…The average error in the [α/Fe] ratio is 0.05 dex. We note that, in general, our derived abundances agree with the [α/Fe] presented in the literature (see Neves et al 2009;Adibekyan et al, in prep. ).…”
Section: α Element Abundancesupporting
confidence: 90%
“…The method and the atomic data are the same as in Neves et al (2009) (see also Adibekyan et al, in prep.). The equivalent widths (EW) were automatically measured with the ARES 3 code (Automatic Routine for line Equivalent widths in stellar Spectra - Sousa et al 2007).…”
Section: α Element Abundancementioning
confidence: 99%
“…The same behaviour was found by Chen et al (2000) and Neves et al (2009), who suggested that SN Ia is possibly contributing. The star HD 50806 is clearly enriched in Mg (and in other elements as well) according to Fig.…”
Section: Abundance Trends As a Function Of [Fe/h]supporting
confidence: 85%
“…The overall trend of our abundance ratios as a function of the stellar metallicity normally follows what has been suggested in the literature concerning the nucleosynthetic origin of the elements and their abundance evolution in time (Chen et al 2000;Reddy et al 2003;Bensby et al 2005;Chen et al 2008;Neves et al 2009). The light metals Ca, Sc, and Ti are predominantly produced by type II Supernovae (SN II) at the beginning of the enrichment history of the Galactic disc.…”
Section: Abundance Trends As a Function Of [Fe/h]supporting
confidence: 83%
See 1 more Smart Citation